Association Between Vaginal Douching and Genital Human Papillomavirus Infection Among Women in the United States. (23rd August 2016) - Bui, Thanh Cong; Thai, Thuy Nhu; Tran, Ly Thi-Hai; Shete, Sanjay S.; Ramondetta, Lois M.; Basen-Engquist, Karen M.
Abstract: The very few studies that have examined the association between vaginal douching and genital human papillomavirus (HPV) infection have found contrary results. We investigated the associations between douching and numbers of HPV genotypes infecting 1271 participants aged 20–49 years in the 2003–2004 US National Health and Nutrition Examination Survey. After controlling for relevant covariates, douching in the past 6 months was significantly associated with infection by higher numbers of all genital HPV types (relative risk ratio, 1.26; 95% confidence interval, 1.03–1.54) and HPV high-risk types (1.40; 1.09–1.80).